Prevalence of sleep-related problems and risks in a community-dwelling older adult population: a cross-sectional survey-based study - Nancy P. Gordon; Jimmy H. Yao; Leslea A. Brickner; Joan C. Lo (BMC, 2022)
Abstract Background Despite evidence of adverse health consequences of inadequate restorative sleep for older adults, assessment of sleep quantity, quality, and use of sleep aids is not routinely done. We aimed to characterize sleep problems, sleep risks, and advice received about sleep in a community-dwelling older adult population, overall and in subgroups with health conditions and functional difficulties. Methods This cross-sectional study used weighted self-report data for 5074 Kaiser Permanente Northern California members aged 65-79y who responded to a 2017 or 2020 Member Health Survey. We estimated usual amount of sleep (< 6, 6 to < 7, ≥7 hours) and prevalence of sleep problems (frequent insomnia, frequent daytime fatigue, poor quality sleep, and potential sleep apnea (OSA) symptoms (frequent very loud snoring, apnea episodes)) for older adults overall, by self-rated health, and in subgroups reporting hypertension, diabetes, heart disease, frequent problems with balance/walking, and frequent memory problems. We also estimated percentages who regularly used sleep aids and had discussed sleep adequacy with a healthcare professional in the past year. Results Approximately 30% of older adults usually got less than the recommended ≥7 hours sleep per day, and 9% experienced frequent daytime fatigue, 13% frequent insomnia, 18% frequent insomnia/poor quality sleep, and 8% potential OSA symptoms. Prevalence of frequent insomnia was higher among women than men (16% vs. 11%). Higher percentages of those in fair/poor health and those with frequent balance/walking and memory problems reported sleeping < 6 hours per day and having all four types of sleep problems. Nearly 20% of all older adults (22% of women vs. 17% of men) and 45% of those with frequent insomnia (no sex difference) reported regular sleep aid use. Only 10% of older adults reported discussing sleep with a healthcare professional whereas > 20% reported discussing diet and exercise. Conclusions Large percentages of older adults experience sleep problems or get less sleep than recommended for optimal sleep health. Older patients should routinely be assessed on multiple components of sleep health (sleep hygiene, quantity, quality, problems, and sleep aid use) and educated about sleep hygiene and the importance of getting adequate restorative sleep for their overall health and wellbeing.